2016
DOI: 10.1039/c6ra24398c
|View full text |Cite
|
Sign up to set email alerts
|

Tailored activated carbons for supercapacitors derived from hydrothermally carbonized sugars by chemical activation

Abstract: Activated carbons (ACs) are actively researched as electrode materials for supercapacitors and there is a significant interest to produce ACs from sustainable and low cost precursors. In this study, various ACs were prepared from hydrothermally carbonized sugars by KOH activation. Both the hydrothermal carbonization and activation processes were optimized to tailor the properties (e.g. textural properties, chemical composition, N-doping, electrical conductivity) of the ACs. For instance, the BrunauerEmmett-Tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…As during electrode manufacturing for EDLCs, additives are added to the active material (Lee et al., ; Liu & Cao, ; Pandolfo & Hollenkamp, ; Zhu et al., ), and the influence of these additives on the EC performance is of great interest. The graphs in Figure show the EC values obtained with M1 (Figure a) and M2 (Figure b) for the pure activated carbon AC‐600‐800 and the same AC plus additives.…”
Section: Resultsmentioning
confidence: 99%
“…As during electrode manufacturing for EDLCs, additives are added to the active material (Lee et al., ; Liu & Cao, ; Pandolfo & Hollenkamp, ; Zhu et al., ), and the influence of these additives on the EC performance is of great interest. The graphs in Figure show the EC values obtained with M1 (Figure a) and M2 (Figure b) for the pure activated carbon AC‐600‐800 and the same AC plus additives.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that KOH activation can destroy the morphology of a precursor to varying degrees. 35,55 Here, the morphologies of the ACs activated in KOH ranged from foam-like (AC-700-K1) to flake-like (AC-800-K4). The foamy morphology of AC-700-K1 could speculatively relate to an activation of the colloidal spheres of HTC-RNA from the inside out, leaving a negative imprint.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…The resulting ACs, labeled AC-X-KY, where X is the activation temperature, and Y is the mass loading of KOH to HTC-RNA, displayed pore textural properties (Table 1) similar to those of KOH-activated ACs prepared from HTC-glucose and HTC-biomass. 28,34,35,38,39,63 AC-700-K1 and -K4, obtained in 33 and 14% yield, respectively, both displayed Activated carbons were derived from hydrothermally carbonized ribonucleic acid (HTC-RNA) by activation for 2 h under flowing N 2 . Samples activated with KOH and KHCO 3 are labeled AC-X-KY and AC-X-KCY, respectively, where X is the activation temperature, and Y is the mass ratio of activating agent to HTC-RNA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…S2b). We have previously observed Fe in activated carbons generated from hydrochars, even when no Fe precursor was added; this is derived from the stainless steel reactor used during the activation 39 .
Figure 3Scanning electron microscope images of activated carbons (ACs) generated from a hydrochar formed in milk without solid precursors. For each sample, a smaller particle is shown on the left, and a larger one on the right.
…”
Section: Resultsmentioning
confidence: 99%